An overview of recent advances and novel synthetic approaches for lignocellulosic derived biofuels - Siddique, Mohammad; Soomro, Suhail Ahmed; Aziz, Shaheen; Akhter, Faheem (Penerbit Universiti Kebangsaan Malaysia, 2021)
One of the most important challenges to overcome at present is to reduce the dependability on the fossil fuels and replace them with green and environmental friendly substitutes. In this respect, biofuel conversion from lignocellulosic materials could prove to be an efficient process. The current review presents the most recent advances and novel synthetic approaches in utilizing lignocellulosic substrates for biofuel production, such as scheming of new/enhanced catalysts, waste valorization, using genetic modifications to improve organism traits, development and/improving the new or step integration processes, etc. Such new strategies can prove to be important tools and augment the use of renewable fuels globally. The present review summarizes the most recent strategies, advances and novel synthetic approaches offered pertaining to catalytic/non-catalytic pretreatments/transformations of lignocellulosic materials, carbohydrates based carbohydrates and technical lignin into biofuels.